If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x = 16x + -8 Reorder the terms: 15x = -8 + 16x Solving 15x = -8 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 15x + -16x = -8 + 16x + -16x Combine like terms: 15x + -16x = -1x -1x = -8 + 16x + -16x Combine like terms: 16x + -16x = 0 -1x = -8 + 0 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8
| 4(x^2+5)=2(x^2+1) | | 18-1/2=6 | | 3*1/8= | | 18x+9=19x+2 | | 3xsquared=9 | | 4(3x+2y)-7x-5(2y-4)= | | 224/32= | | 3(-4m-6)=-6(m+3) | | 30*93= | | -38-7k=-8(k+4) | | 32/224 | | -2x-1=-9x-x | | 5/9=1/4x | | 25*79= | | 26x=27x-5 | | 2y^3+3y^2=0 | | 5x+10y=-2 | | 157=-192+h | | 11*38= | | -2z/2 | | 4f-9-3f+10= | | -18=-15-3(6t+5) | | 0(5m)=5m | | -x+3+3x=-19 | | 3=(3+2x)-2(1+3x) | | x-44=90 | | 6-4(x-1)=3x+2(x+5) | | 15*44= | | 12x+6=13x-1 | | 11y+2y= | | -(-40)+m=65 | | 3(y-2)=6y+1-2(-6y-1) |